Odpowiedzi

2010-03-12T17:08:49+01:00
3(a-1)+a= 3a-3+a = 4a-3
-5(b+8)-2b = -5b-40-2b = -7b-40
4(ab-2b) = 4ab-8b
-7(-b+(-ba) = -7(-b-ba) = 7b+7ab
(-2)*(2c+(-5)b) = (-2)*(2bc-5b) = -4bc+10b
0,5(4a+(-6)b) = 0,5(4a-6b) = 2a-3b
2010-03-12T17:10:35+01:00
=3a-3+a=4a-3



=-5b-40-2b=-7b-40



=4ab-8b



=7b+7ba




=0.5(4a-6b)=2a-3b
2010-03-12T17:12:48+01:00
3(a-1)+a= 3a-3+a=4a-3
-5(b+8)-2b= -5b-40-2b=-7b-40
4(ab-2b)= 4ab-8b
-7(-b+(-ba))=-7(-b-ba)= 7b+7ba
(-2)*(2c+(-5)b)= -2*(2c-5b)= -4c+10b
0,5(4a+(-6)b) =2a-3b
1 5 1